3次方程式の標準形

3次方程式の標準形

3次方程式\(a_{3}\ne0\)

\[ a_{3}x^{3}+a_{2}x^{2}+a_{1}x+a_{0}=0 \]

は以下のように変形できる。

\[ X^{3}+pX+q=0 \]

ただし、

\[ \begin{cases} X=x+\frac{a_{2}}{3a_{3}}\\ p=\frac{3a_{1}a_{3}-a_{2}^{\;2}}{3a_{3}^{\;2}}\\ q=\frac{3^{3}a_{0}a_{3}^{\;2}+2a_{2}^{\;3}-9a_{1}a_{2}a_{3}}{3^{3}a_{3}^{\;3}} \end{cases} \]

である。

\begin{align*} a_{3}x^{3}+a_{2}x^{2}+a_{1}x+a_{0} & =a_{3}\left(x^{3}+\frac{a_{2}}{a_{3}}x^{2}+\frac{a_{1}}{a_{3}}x+\frac{a_{0}}{a_{3}}\right)\\ & =a_{3}\left\{ \left(x+\frac{a_{2}}{3a_{3}}\right)^{3}-3\left(\frac{a_{2}}{3a_{3}}\right)^{2}x-\left(\frac{a_{2}}{3a_{3}}\right)^{3}+\frac{a_{1}}{a_{3}}x+\frac{a_{0}}{a_{3}}\right\} \\ & =a_{3}\left\{ \left(x+\frac{a_{2}}{3a_{3}}\right)^{3}+\left(\frac{3a_{1}a_{3}-a_{2}^{\;2}}{3a_{3}^{\;2}}\right)x+\frac{3^{3}a_{0}a_{3}^{\;2}-a_{2}^{\;3}}{3^{3}a_{3}^{\;3}}\right\} \\ & =a_{3}\left\{ \left(x+\frac{a_{2}}{3a_{3}}\right)^{3}+\left(\frac{3a_{1}a_{3}-a_{2}^{\;2}}{3a_{3}^{\;2}}\right)\left(x+\frac{a_{2}}{3a_{3}}\right)-\frac{3a_{1}a_{3}-a_{2}^{\;2}}{3a_{3}^{\;2}}\frac{a_{2}}{3a_{3}}+\frac{3^{3}a_{0}a_{3}^{\;2}-a_{2}^{\;3}}{3^{3}a_{3}^{\;3}}\right\} \\ & =a_{3}\left\{ \left(x+\frac{a_{2}}{3a_{3}}\right)^{3}+\left(\frac{3a_{1}a_{3}-a_{2}^{\;2}}{3a_{3}^{\;2}}\right)\left(x+\frac{a_{2}}{3a_{3}}\right)+\frac{3^{3}a_{0}a_{3}^{\;2}+2a_{2}^{\;3}-9a_{1}a_{2}a_{3}}{3^{3}a_{3}^{\;3}}\right\} \end{align*}

これより、

\[ \begin{cases} X=x+\frac{a_{2}}{3a_{3}}\\ p=\frac{3a_{1}a_{3}-a_{2}^{\;2}}{3a_{3}^{\;2}}\\ q=\frac{27a_{0}a_{3}^{\;2}+2a_{2}^{\;3}-9a_{1}a_{2}a_{3}}{27a_{3}^{\;3}} \end{cases} \]

とおくと、

\begin{align*} 0 & =a_{3}x^{3}+a_{2}x^{2}+a_{1}x+a_{0}\\ & =a_{3}\left\{ X^{3}+pX+q\right\} \end{align*}

両辺を\(a_{3}\)で割って、

\[ X^{3}+pX+q=0 \]

となる。

ページ情報

タイトル

3次方程式の標準形

URL

https://www.nomuramath.com/wr4pkfdl/

SNSボタン